Engagement and Arousal effects in predicting the increase of cognitive functioning following a neuromodulation program - Pino, Olimpia; Romano, Graziana (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Research in the field of Brain-Computer Interfaces (BCIs) has increased exponentially over the past few years, demonstrating their effectiveness and application in several areas. The main purpose of the present paper was to explore the relevance of user engagement during interaction with a BCI prototype (Neuro-Upper, NU), which aimed at brainwave synchronization through audio-visual entrainment, in the improvement of cognitive performance. Methods: This paper presents findings on data collected from a sample of 18 subjects with clinical disorders who completed about 55 consecutive sessions of 30 min of audio-visual stimulation. The relationship between engagement and improvement of cognitive function (measured through the Intelligence Quotient - IQ) during NU neuromodulation was evaluated through the Index of Cognitive Engagement (ICE) measured by the Pope ratio (Beta / (Alpha + Theta), and Arousal [(High Beta + Low Beta) / (High Alpha + Low Alpha)]. Results: A significant correlation between engagement and IQ improvement, but no correlation between arousal and IQ improvement emerged, as expected. Conclusions: Future research aiming at clarifying the role of arousal in psychological disorders and related symptoms will be essential.